DISCUSSION ON HUMAN SECURITY (HEALTH SECURITY) OF THE COVID-19 PANDEMIC IN INDONESIA: BIBLIOMETRIC ANALYSIS AND VISUALIZATION ARTICLE INDEXED IN SCOPUS - Yeyen Subandi; Diansari Solihah Amini; Tanti Nurgiyanti; Bagus Subekti Nuswantoro; Harits Dwi Wiratma; Maria Veri Diana Baun Yuel (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This research was conducted to look at the human security disaster management of the Covid-19 pandemic in Indonesia which is indexed by Scopus. Referring to the United Nations Development Program (UNDP) statement regarding human security, there are seven areas, namely: Regarding the health security sector, the environmental security sector, the food security sector, the economic security sector, the individual security sector, the community security sector, and the political security sector. Of the seven areas, one of them is the problem of health resilience, and the Covid-19 Pandemic is included in the category of health security. UNDP defines health insurance as protection from disease and unhealthy lifestyles, which threaten inadequate health services, new and recurring diseases including epidemics, and pandemics, malnutrition, and unsafe lifestyles. Until this article was written, there has been no research that has seen that the Covid-19 Pandemic is part of a human security disaster, which is more specifically included in the health security category. In this study, data was taken online through the Scopus database which was then analyzed using the VOSviewer bibliometric visualization. The findings in this study are that the human security disaster during the Covid-19 pandemic is a problem in the field of human health security which is included in the human security category according to UNDP. Until now there has not been much research conducted by academics and researchers from Indonesia, because they only found 25 article documents